Cellular beam design for resistance to inelastic lateral–torsional buckling - Panedpojaman, Pattamad; Sae-Long, Worathep; Chub-uppakarn, Tanan (Thin-walled structures, 2016)
To facilitate accurate but conservative design of cellular beams for resistance against lateral–torsional buckling (LTB), this study proposes rational design guidelines based on General method of EC3. The inelastic LTB resistance was the subject of parametric studies using nonlinear finite elements, covering various loading configurations and geometric parameters of practical cellular beams. End moment and shear loadings were considered. The design resistance is slightly conservative in cases with complete LTB behavior that is generally found with non-dimensional slenderness exceeding 2.50. With short beams and shear loads LTB failure may interact with the local failures web-post buckling and web distortional buckling. However, combinations of LTB and Vierendeel failure were not observed. Concentrated stresses in the flange occur with short beams and moment loads, and these can degrade the LTB resistance. Due to interactions of the local failures in short beams, the design resistance requires a correction to ensure it is conservative. The key parameters affecting resistance include load configuration, section ratio, spacing ratio, and slenderness. All these parameters reflect shear effects, but section ratio and slenderness significantly influence the accuracy of the design results. Therefore, a correction factor based on these parameters is proposed, such that improves the EC3 accuracy by minimizing overestimation. The proposed LTB resistance design approach remains mostly conservative relative to both FE simulations and experimental results. •Inelastic LTB resistances of cellular beams are investigated by Nonlinear FE models.•Shear effects and geometric parameters of practical cellular beams are considered.•With short beams and shear loads, LTB failures may interact with the local failures.•The resistance of EC3 design requires a correction to ensure its conservative.•A correction factor based on the parameters reflecting shear effects is proposed.